Kepemimpinan dalam Administrasi Pendidikan - Novita Sari Nasution; Nurhaliza Ertays Siregar; Putri Puspitasari (Universitas Maritim AMNI Semarang, 2024)
Leadership in educational administration is a crucial aspect in achieving effective and efficient educational goals. This article aims to deeply examine various aspects of leadership in educational administration, including understanding, necessary skills, applied leadership styles, and specific functions that leaders must perform. The research method used is literature review, encompassing analysis of various literature and previous studies related to educational leadership. The research findings indicate that effective leadership in educational administration requires a combination of technical skill, human skill, and conceptual skill, along with the application of leadership styles suitable to the institutional context. Leadership functions such as planning, organizing, directing, and controlling are also crucial to ensure efficient operations and goal achievement. The implications of this study provide insights and practical recommendations for educational leaders to enhance the performance and quality of their institutions, as well as to create an environment that supports learning and growth.